One uncertainty added on top of another: Challenges and resources of mothers of preterm infants during the COVID-19 pandemic - Shoshi, Palmor Haspel; Tuval-Mashiach, Rivka; Bin Nun, Alona (Frontiers in Psychology, 2022)
Aims and objectives: To qualitatively explore COVID-19-related experiences of mothers of preterm infants in the NICU, the main challenges they face, and the resources available for them. Background: The birth of a preterm infant is a stressful event under otherwise normal circumstances. The outbreak of COVID-19, the uncertainty about the virus and how it spreads, and the restrictions imposed, may have exacerbated the stress of caring for a preterm infant. Design: Retrospective interviews. Method: In-depth interviews with 12 mothers of preterm infants who were hospitalized in the Neonatal Intensive Care Unit (NICU) at the time of study. The interview addressed challenges and resources related to coping with the pandemic. The interviews were transcribed and content analyzed, based on the model for narrative analysis. This research was conducted in accordance with the COREQ checklist. Results: The overarching experience shared by all mothers was accumulative stress caused by a combination of factors related to the infant's health and COVID-19-related stressors. A central theme was the dissonance between the mothers' expectations from the birth and infant, and the reality they encountered. Other themes included fear of infecting the infant, loneliness, and stress caused by the restrictions that disrupted daily routines. Resources included a sense of shared fate regarding the pandemic, improvements in the infant's condition, religious faith, emotional support from the partner, and support from professional staff. Conclusion: Caring for a preterm infant during a pandemic is a challenging experience on many levels. The loss of significant support resources puts mothers of these infants at a higher risk for psychological distress.